Application Of Response Surface Methodology (RSM) For Optimization Paramter Of LSCF-CuO For Intermediate Temperature Solid Oxide Fuel Cells - John, Jonathon (Universiti Sains Malaysia, 2021)
Optimization of lanthanum strontium cobalt ferrite mixed with copper (II) oxide (LSCF-CuO) for the synthesis condition is carried out to maximize the fuel performance. The optimization is carried out using Response Surface Methodology; Central composite design (CCD), Historical data and Optimal-D models in the Design-Expert (12) software and the comparison between them have been made. The optimization was carried over a done experiment to analyze the parameters, sintering temperature (°C) and CuO concentration (wt%) on the polarization resistance Ωcm-2 which indirectly affect the fuel cell performance. The adequacy analysis for all the 3 designs shows normal distribution plot which indicate the accuracy of the quadratic to predict the response. Based on ANOVA analysis for all the 3 designs, p value of less than 0.05 for the sintering temperature and CuO concentration indicate a significant effect of these parameters on the polarization resistance. Based on the fit summary analysis, the designs shows good fit of quadratic models since the R2 for CCD, Historical data and Optimal-D are 0.9911, 0.9936 and 0.9959 respectively (close to unity). The aim of the optimization is to minimize the polarization resistance and therefore Optimal-D model shows the good optimization result since it exhibit the lowest Rp of 0.11 Ωcm-2 compared to Historical data (0.16 Ωcm-2 ) and CCD (0.12 Ωcm-2 ). The optimized sintering temperature and CuO concentration for Optimal-D were 656 °C and 1.65 wt % respectively.